USING DIGITAL TECHNOLOGIES IN THE WORK OF ACADEMIC GROUP CURATORS IN HIGHER EDUCATION INSTITUTIONS - SKIDAN, VLADYSLAVA; VOLIVACH, ANTONINA; NIKONOV, OLEH; MYTELSKA, OLENA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The rapid development of modern digital technologies and the development of mobile applications, with their subsequent implementation, enhance communication skills and the solution of complex tasks in society, especially in organizing the educational activities of higher education institutions Therefore, the use of digital technologies in the work of academic group curator represents an important and relevant direction in modern education. Here are several key aspects that highlight the importance of this initiative: Convenience and accessibility: The mobile application allows curators to easily access necessary information and tools through their smartphones. This provides instant access to important data and simplifies the workflow. Effective management: The application provides curators with tools for effectively tracking students academic progress. They can quickly analyze data and make management decisions based on objective information. Improved communication: Digital technologies streamline communication among curators, students, and parents. Through chats, messaging, and email, curators can easily communicate and share information. Workflow optimization: The application contributes to optimizing the workflow of curators. They can quickly find the necessary information, complete tasks, and increase the efficiency of their work. Improvement of the educational process: By tracking students progress, curators can provide individual support and recommendations to enhance academic achievements. Interactions with parents: The application allows curators to engage parents in the educational process by sending them reports and information about their children performance. Analysis and planning: Data analysis tools in digital technologies help curators make informed decisions and plan future activities. The use of digital technologies in the work of an academic group curator improves management and the educational process, as well as enhances communication and work efficiency.